Dynamic Oligopoly and Price Stickiness - Wang, Olivier; Werning, Iván (American Economic Review, 2022)
How does market concentration affect the potency of monetary policy? To address this question we embed a dynamic oligopolistic game into a general-equilibrium macroeconomic model. We provide a sufficient-statistic formula for the response to monetary shocks involving demand elasticities, concentration and markups. We discipline our model with evidence on pass-through and find that higher concentration amplifies nonneutrality and stickiness. We isolate strategic effects from oligopoly by comparing our model to one with naive firms. We derive an exact Phillips curve featuring novel higher-order terms, but show that a standard New Keynesian one recalibrated with higher stickiness provides an excellent approximation. (JEL D43, E12, E21, E31, E43, E51, E52)